The Spider Sapphire Mystery - Keene Carolyn; Carolyn Keene (New York Carolyn Keene, 1968)
Nancy travels to East Africa on safari to clear Floyd Ramsay, her father$1 (Bs client accused of stealing a rare spider-embedded sapphire. While navigating dangers, she uncovers a smuggling ring, finds a missing guide, and thwarts blackmailer enemies.s
Keywords: The Spider Sapphire Mystery (Nancy Drew Mystery Stories #45) by Carolyn Keene centers on the following key elements of the plot and character actions; (Nancy Drew Mystery Stories #45) by Carolyn Keene centers on the theft of a unique gem, a missing safari guide, and a blackmail plot, offering several moral lessons typical of the series' "wholesome" adventure genre